PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PARFUM THE BODY SHOP BODY MIST JAPANESE CHERRY BLOSSOM PADA TOKO THE BODY SHOP PALANGKA RAYA - Tasman H. Taher; Pamungkur Pamungkur; Sunarmie Sunarmie (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this research was to determine the effect of word of mouth on purchasing decisions of the body shop japanese cherry blossom body mist product at the body shop shop in Palangka Raya. The method used is a quantitative method with a simple linear regression analysis tool and assisted by SPSS. The population of this research is the customers of the body shop body mist japanese cherry blossom products in Palangka Raya, the sample is 30 people. The results showed that word of mouth had an effect on purchasing decisions for the body shop body shop body mist japanese cherry blossom product at the body shop shop in Palangka Raya.